Effects of an Electronic Medical Records-Linked Diabetes Self-Management System on Treatment Targets in Real Clinical Practice: Retrospective, Observational Cohort Study - Yang, So Jung; Lim, Sun-Young; Choi, Yoon Hee; Lee, Jin Hee; Yoon, Kun-Ho (Endocrinology and metabolism (Seoul), 2024)
Background: This study evaluated the effects of a mobile diabetes management program called “iCareD” (College of Medicine, The Catholic University of Korea) which was integrated into the hospital’s electronic medical records system to minimize the workload of the healthcare team in the real clinical practice setting.Methods: In this retrospective observational study, we recruited 308 patients. We categorized these patients based on their compliance regarding their use of the iCareD program at home; compliance was determined through self-monitored blood glucose inputs and message subscription rates. We analyzed changes in the ABC (hemoglobin A1c, blood pressure, and low-density lipoprotein cholesterol) levels from the baseline to 12 months thereafter, based on the patients’ iCareD usage patterns.Results: The patients comprised 92 (30%) non-users, 170 (55%) poor-compliance users, and 46 (15%) good-compliance users; the ABC target achievement rate showed prominent changes in good-compliance groups from baseline to 12 months (10.9% vs. 23.9%, P<0.05), whereas no significant changes were observed for poor-compliance users and non-users (13.5% vs. 18.8%, P=0.106; 20.7% vs. 14.1%, P=0.201; respectively).Conclusion: Implementing the iCareD can improve the ABC levels of patients with diabetes with minimal efforts of the healthcare team in real clinical settings. However, the improvement of patients’ compliance concerning the use of the system without the vigorous intervention of the healthcare team needs to be solved in the future.